(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
In the oil and gas business, flow assurance is a relatively recent word. Flow assurance refers to a low cost method of producing and transporting fluids from a reservoir to a processing facility. The growing demand of energy has led oil companies to move towards exploration in offshore deep water sand remote places, under extreme environmental conditions. Owing to such harsh environmental conditions, oil companies have to face critical operational challenges during production and transportation of crude oil. One of such menace is flow assurance issues. Stream confirmation issues contrarily affect well consummation plan and creation working procedures. Hydrates, wax affidavit, naphthenates, asphaltenes, consumption, scales, slugging, and emulsion are all stream confirmation challenges. For stream confirmation, hydrates and wax testimony are basic difficulties that should be tended to first. This paper portrays the stream confirmation challenges that impact unrefined petroleum transportation from the repository to the retail location, both coastal and seaward, in chilly environments. The paper also represents the process mechanism and mitigation methods used for each fluid flow assurance issue. It is impossible to overstate the significance of flow assurance in the oil as well as gas business. Failure of flow assurance can result in catastrophic consequences, such as the loss of resources or even lives.